Expression of exogenous dsRNA by Lecanicillium attenuatum enhances its virulence to Dialeurodes citri. Issue 4 (31st October 2018) - Yu, Shi‐Jiang; Pan, Qi; Luo, Ren; Wang, Cui‐Lun; Cheng, Lu‐Yan; Yang, Juan‐Sheng; Zhou, Hao‐Nan; Hou, Dong‐Yuan; Liu, Hao‐Qiang; Ran, Chun
Abstract: BACKGROUND: Dialeurodes citri is an important pest in citrus‐producing areas of the world. Lecanicillium attenuatum parasitizes D. citri and kills it, suggesting a potential approach for the biological control of pests. However, the low virulence of the fungus and its slow rate of killing have limited its commercial competitiveness. The objective reason for these disadvantages is immunological rejection by the host. Our strategy was to use fungi to express the double‐stranded RNA (dsRNA) of the host immune genes. The fungal hyphae release siRNA at the time of infection, thus interfering with the expression of immune genes in the host and facilitating fungal invasion. RESULTS: We selected prophenoloxidase ( DcPPO ), prophenoloxidase‐activating factor ( DcPPO‐AF ), and lysozyme ( DcLZM ) as target genes to construct intron‐splicing hairpin RNA expression vectors and to successfully obtain transgenic fungi. Two days after infection, the immune genes of D. citri showed varying degrees of silencing compared with those in the positive control group. The median lethal concentration (LC50 ; spores mL −1 ) values of La::GFP, La::DcPPO, La::DcPPO‐AF, and La::DcLZM were 9.63 × 10 4, 2.66 × 10 4, 1.21 × 10 5, and 3.31 × 10 4, respectively. The 50% lethal time (LT50 ) values of these fungi were 5.15, 3.60, 5.34, and 4.04 days, respectively. The virulence of La::DcPPO and La::DcLZM increased 3.62‐ and 2.91‐fold, respectively, and their LT50 decreased by 30.10% and 21.55%, respectively. CONCLUSIONS: The results indicate that this method, which uses tens of thousands of hyphae to inject dsRNA to improve the virulence of transgenic fungi, can play a greater role in the prevention and control of pests in the future. © 2018 Society of Chemical Industry Abstract : This method, which uses tens of thousands of hyphae to inject double‐stranded RNA (dsRNA) to improve the virulence of transgenic fungi, can play a greater role in the prevention and control of pests in the future.